2005
DOI: 10.1016/s1726-4901(09)70155-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Prolonged Postoperative Pleural Effusion After Repair of Tetralogy of Fallot

Abstract: Prolonged PE is a significant morbidity after TOF repair. The risk factors for prolonged PE are gender, age at repair, body weight, bypass time, low oxygen saturation before surgery, wound infection after surgery, duration of endotracheal intubation, length of hospital stay, and Nakata index. Oxygen saturation before surgery and wound infection were major risk factors while age at repair was a confounder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…20 Several risk factors, including cardiopulmonary bypass (CPB) time, low oxygen saturation preoperatively, wound infection, and longer duration of mechanical ventilation, would cause prolonged pleural effusion after TOF repair. 19 Sasson et al 14 found a longer CPB time in the group with monocusp valve reconstruction, but shorter duration of pleural drainage in this group. Singh et al 21 also found a longer CPB time in the monocusp group, but no difference in the duration of postoperative pleural drainage between these two groups.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…20 Several risk factors, including cardiopulmonary bypass (CPB) time, low oxygen saturation preoperatively, wound infection, and longer duration of mechanical ventilation, would cause prolonged pleural effusion after TOF repair. 19 Sasson et al 14 found a longer CPB time in the group with monocusp valve reconstruction, but shorter duration of pleural drainage in this group. Singh et al 21 also found a longer CPB time in the monocusp group, but no difference in the duration of postoperative pleural drainage between these two groups.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, the design of the monocusp valve, including both the size and material, would also affect the function of this valve. 16,19,26 Therefore, we could suppose that the insertion of a monocusp valve might not be indicated in all children with TOF in whom a TAP is considered as the surgical technique. The experience of the cardiovascular surgeon and the criteria of patient selection may also play important roles in achieving better postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged effusions are reported in between 7.3 and 13.5% of operated tetralogy of Fallot patients and may be viewed as a disruption of the fluid equilibrium [20,21]. The mechanism behind is likely multifactorial and a combination of changed physiology and the trauma of the operation.…”
Section: Lymphatic Effusion and Chylothoraxmentioning
confidence: 99%
“…[89] Systemic venous hypertension is often reflected by high right atrial pressures following repair of TOF, which increases the mean capillary hydrostatic pressure, leading to accumulation of excessive fluid in the pleural space. [10] In addition many of these patients may have borderline pulmonary artery and peripheral pulmonary artery stenosis, which leads to elevated right atrial pressures.…”
Section: Pathophysiologymentioning
confidence: 99%
“…[10] In addition many of these patients may have borderline pulmonary artery and peripheral pulmonary artery stenosis, which leads to elevated right atrial pressures. [810] The presence of residual tricuspid insufficiency, compounds the problem of right heart failure. In patients with TOF and other forms of cyanotic heart disease, the pulmonary vascular anatomy is often abnormal.…”
Section: Pathophysiologymentioning
confidence: 99%